PELAKSANAAN DIET DAN STATUS GIZI SERTA KEMANDIRIAN PENDERITA HIPERTENSI LANSIA DI DESA BONTO MARANNU - Hendrayati Hendrayati; Putri Indah Nirmalasari (Media Gizi Pangan, 2019)
ABSTRACTIncreased Life Expectancy (UHH) in Indonesia is a success in the field of health and welfare. UHH can increase the elderly population (elderly) by decreasing mortality. The 2015 Central Bureau of Statistics (BPS) report, UHH in 2015 became 70.8 years and will increase to 72.2 years in 2030-2035, while in Maros district in 2015 for UHH increased to 68.55 years. The aging process in the elderly has the risk of non-communicable diseases, such as hypertension. The results of the Basic Health Research (Riskesdas) in 2013, showed that the health problems in the highest elderly were Hypertension with the category age of 55-64 years of 45.9%, 65-74 years of 57.6% and 75 years and over 63.8 %.Hypertension in the elderly can affect the level of dependence on the surrounding environment. The dependency ratio of Indonesia's elderly population in 2016 was 13.65%. This means that every 100 people of productive age must bear about 14 elderly residents. The dependency ratio in South Sulawesi is 14.62%, which means that every 100 productive residents in South Sulawesi must bear around 15 elderly residentsThis study is an analytical study with a cross sectional study design. The population in this study were all elderly  aged 60-80 years. Sampling using purposive sampling with sample criteria as follows: 60 - 80 years old, have a history of hypertension and / or have high blood pressure (≥ 140/90 mmHg) at the time of measurement, Willing to be interviewed, Not having hearing and memory disorders (senile) and can be invited to communicate clearly. Samples that fit the criteria in this study were 47 people.Research result is a disobedience to the hypertension diet in elderly people with very high hypertension reaches 91.5%, and insignificant relationship between nutritional status and the independence of the elderly both the age group <75 years and the age group ≥75 years with a significant value of each p = 0.619 and p = 0.191.There is a non-significant relationship between hypertension and the independence of the elderly both in the age group <75 years and the age group ≥75 years with a significant value of p = 0.447 and p = 0.362.The elderly with hypertension sufferers should always be given counseling and / or nutritional consultation to increase their understanding of the diet being undertaken